Sand consolidation agent with high permeability
Patent Information
- Application Number
- CN202411513512.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-28
AI Technical Summary
出砂问题较为严重时会堵塞油气通道,造成油气井大幅降产甚至停产的结果
[0012]正是因为采用上述方案,本发明的固砂剂保持高固砂胶结性能的同时还能具有很高的渗透率保持率(>80%,60℃,24h),使用本产品得到的胶结岩心抗压强度高(>5.0MPa,300℃,48h)同时具有优良的耐高温性能,在高温油气层固砂也能保持较高的渗透率(>500×10-3μm2,300℃,24h),提高油田开采的效率和安全性。
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oilfield chemistry, and in particular relates to a sand consolidating agent with high permeability. Background Art
[0002] Sand production refers to the phenomenon that formation sand flows into the wellbore during the production process of water injection and oil recovery in oil and gas wells due to pressure difference damage, loose rock cementation of sandstone oil and gas layers, etc. When the sand production problem is more serious, it will block the oil and gas channels, resulting in a significant reduction in oil and gas well production or even shutdown. In order to solve the problem of sand production in oil and gas wells, it is necessary to add sand consolidating agents to consolidate the sand particles through the cementation effect between the formation particles to suppress the sand production phenomenon. For high-temperature and high-pressure formations, higher requirements are placed on the cementation effect of sand consolidating agents. On the other hand, sand consolidating agents with strong cementation effect often have poor porosity increase effect. Therefore, most of the sand consolidating agent products on the market will have the problem of insufficient permeability retention rate when used in high-temperature and high-pressure oil layers, which will cause the oil and gas well production to decrease due to the low permeability of the oil and gas layer. Summary of the invention
[0003] The purpose of the present invention is to provide a high-permeability sand consolidating agent to solve the problem of insufficient permeability retention of a strong cementing sand consolidating agent. The sand consolidating agent can effectively inhibit sand production in oil and gas wells and maintain high permeability.
[0004] In order to achieve the above-mentioned object, the present invention provides a high-permeability sand consolidating agent, which comprises agent A and agent B. Agent A comprises the following components: N, N', N"-trimethyldiethylenetriamine, deionized water, amidopropyl hydroxysulfonyl betaine viscoelastic surfactant and N, N, N', N'-tetramethyl-1, 3-butanediamine; agent B comprises the following components: triethylene glycol monobutyl ether, methyl methacrylate-butadiene-styrene terpolymer and MF-3285 trifunctional alicyclic epoxy resin. In agent A, N, N', N"-trimethyldiethylenetriamine is used as a curing main agent, deionized water is mainly used to promote the micellization effect of amidopropyl hydroxysulfonyl betaine viscoelastic surfactant, and amidopropyl The hydroxysulfonyl betaine viscoelastic surfactant is mainly used as a pore-increasing agent, and N,N,N',N'-tetramethyl-1,3-butanediamine is used as a curing auxiliary and a pore-increasing auxiliary. In particular, the combination of N,N,N',N'-tetramethyl-1,3-butanediamine and amidopropyl hydroxysulfonyl betaine viscoelastic surfactant can make amidopropyl hydroxysulfonyl betaine viscoelastic surfactant play a better pore-increasing role; in agent B, MF-3285 trifunctional alicyclic epoxy resin is used as a resin adhesive, methyl methacrylate-butadiene-styrene terpolymer is used as a toughening agent, and triethylene glycol monobutyl ether is used as a solubilizer for methyl methacrylate-butadiene-styrene terpolymer and a dispersant for the sand-fixing agent. Agents A and B in the sand-fixing agent are independent of each other. When used, they are stirred and mixed according to a certain range of mass ratios. The mass ratio of agent A to agent B is 1.00:(1.06-1.33).
[0005] Preferably, by weight percentage, agent A comprises the following components: 67%-70% of N,N',N"-trimethyldiethylenetriamine, 19%-21% of deionized water, 4%-5% of amidopropylhydroxysulfonyl betaine viscoelastic surfactant, 6%-8% of N,N,N',N'-tetramethyl-1,3-butanediamine, and the total of the above components is 100%; agent B comprises the following components: 6%-10% of triethylene glycol monobutyl ether, 3%-4% of methyl methacrylate-butadiene-styrene terpolymer, and 86%-91% of MF-3285 trifunctional alicyclic epoxy resin, and the total of the above components is 100%.
[0006] Preferably, the amidopropyl hydroxysulfonyl betaine viscoelastic surfactant is selected from erucic acid amidopropyl hydroxysulfonyl betaine. The concentration of the erucic acid amidopropyl hydroxysulfonyl betaine is 40%.
[0007] The present invention also provides a method for preparing the above-mentioned high-permeability sand consolidating agent, comprising the following steps:
[0008] Production process of agent A: weigh the raw materials according to the ratio, pour N,N',N"-trimethyldiethylenetriamine into the reactor, and start stirring at a speed of 60r-100r / min, keep the temperature at 15℃-40℃, add deionized water and amidopropyl hydroxysulfonyl betaine viscoelastic surfactant to the reactor, stir for 0.5-1.0h, then add N,N,N',N'-tetramethyl-1,3-butanediamine, continue stirring for 0.5-1.0h, and the light yellow micro-colloidal liquid obtained is agent A of high permeability sand consolidating agent;
[0009] Production process of Agent B: Weigh the raw materials according to the ratio, add triethylene glycol monobutyl ether into the reactor, start heating, and start stirring at a speed of 90r-130r / min. When the temperature reaches 45°C, add methyl methacrylate-butadiene-styrene terpolymer, maintain the temperature at 45°C-52°C, stir for 0.5-1.0h, then pour MF-3285 trifunctional alicyclic epoxy resin into the reactor, continue stirring for 0.5-1.0h, cool to room temperature, and the resulting light yellow viscous liquid is Agent B of the high permeability sand consolidating agent.
[0010] The present invention also provides application of the high-permeability sand consolidating agent in oil well sand prevention.
[0011] When used specifically, the method comprises the following steps: mixing agent A and agent B of the sand consolidating agent in a mass ratio of 1.00:(1.06-1.33).
[0012] It is precisely because of the adoption of the above scheme that the sand consolidation agent of the present invention can maintain high sand consolidation and cementation performance while also having a high permeability retention rate (>80%, 60°C, 24h). The cemented core obtained by using this product has high compressive strength (>5.0MPa, 300°C, 48h) and excellent high temperature resistance. It can also maintain a high permeability (>500×10 -3 μm 2 , 300℃, 24h), improving the efficiency and safety of oil field exploitation. DETAILED DESCRIPTION
[0013] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0014] The present invention provides a technical solution: a sand consolidating agent with high permeability.
[0015] Raw materials used in each example: EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine, purchased from Shanghai Yincong New Material Technology Co., Ltd., erucic acid amide propyl hydroxysulfonyl betaine content of 40%; XT 100 type methyl methacrylate-butadiene-styrene terpolymer was purchased from Arkema.
[0016] Embodiment 1:
[0017] The sand consolidating agent is divided into A and B. A and B are independent of each other during production but are used in combination. A comprises the following components: 67 kg N,N',N"-trimethyldiethylenetriamine, 20 kg deionized water, 5 kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine, 8 kg N,N,N',N'-tetramethyl-1,3-butanediamine, and the total of the above components is 100 kg; B comprises the following components: 10 kg triethylene glycol monobutyl ether, 4kg of XT 100 type methyl methacrylate-butadiene-styrene terpolymer, 86kg of MF-3285 type trifunctional alicyclic epoxy resin, and the total weight of the above components is 100kg.
[0018] Obtained as follows:
[0019] Weigh the raw materials according to the ratio, pour 67kg N,N',N"-trimethyldiethylenetriamine into the reactor, start stirring at a speed of 80r / min, keep the temperature at 25℃-35℃, add 20kg deionized water and then 5kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine into the reactor, stir for 0.5h, then add 8kg N,N,N',N'-tetramethyl-1,3-butanediamine, continue stirring for 1.0h, and the light yellow micro-colloidal liquid obtained is the A agent of the high permeability sand consolidating agent;
[0020] Weigh the raw materials according to the ratio, add 10kg of triethylene glycol monobutyl ether into the reactor, start heating, and start stirring at a speed of 130r / min. When the temperature reaches 45℃, add 4kg XT 100 type methyl methacrylate-butadiene-styrene terpolymer, maintain the temperature at 45℃-52℃, stir for 0.5h, then pour 86kg MF-3285 type trifunctional alicyclic epoxy resin into the reactor, continue stirring for 1.0h, cool to room temperature, and the obtained light yellow viscous liquid is Agent B of the high permeability sand consolidating agent.
[0021] Afterwards, the samples were tested. When testing the samples in all the embodiments, the A and B agents of the sand consolidating agent were first stirred and mixed as a whole and added to the quartz sand to prepare the cemented core, wherein the mass ratio of the A and B agents was 1.00:1.20, and the mass of the sand consolidating agent was 5% of the mass of the quartz sand. The compressive strength related indicators were tested with reference to Q / SH 10201969-2016 "General Technical Conditions for Sand Consolidating Agents"; the permeability related indicators were tested with reference to SY / T 6572-2003 "Performance Evaluation Method of Resin for Sand Control". The subsequent embodiments will not be repeated.
[0022] Example 1 The performance index test of the sand consolidation agent sample is as follows Table 1
[0023] Table 1
[0024] project index Cemented core compressive strength (60℃, 48h, MPa) 6.1 High temperature cemented core compressive strength (300℃, 48h, MPa) 5.6 Permeability retention rate (60℃, 24h, %) 87 <![CDATA[Core permeability after cementation (60°C, 24 h, 10 -3 μm 2 )]]> 482 <![CDATA[Core permeability after high-temperature cementation (300 °C, 24 h, 10 -3 μm 2 )]]> 597
[0025] Embodiment 2:
[0026] The sand consolidating agent is divided into A and B. A and B are independent of each other in production but are used in combination. A comprises the following components: 70 kg N,N',N"-trimethyldiethylenetriamine, 20 kg deionized water, 4 kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine, 6 kg N,N,N',N'-tetramethyl-1,3-butanediamine, and the total of the above components is 100 kg; B comprises the following components: 6 kg triethylene glycol monobutyl ether, 3kg of XT 100 type methyl methacrylate-butadiene-styrene terpolymer, 91kg of MF-3285 type trifunctional alicyclic epoxy resin, and the total weight of the above components is 100kg.
[0027] Obtained as follows:
[0028] Weigh the raw materials according to the ratio, pour 70kg N,N',N"-trimethyldiethylenetriamine into the reactor, start stirring at a speed of 80r / min, keep the temperature at 25℃-35℃, add 20kg deionized water and then 4kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine into the reactor, stir for 0.5h, then add 6kg N,N,N',N'-tetramethyl-1,3-butanediamine, continue stirring for 1.0h, and the light yellow micro-colloidal liquid obtained is the A agent of the high permeability sand consolidating agent;
[0029] Weigh the raw materials according to the ratio, add 6kg of triethylene glycol monobutyl ether into the reactor, start heating, and start stirring at a speed of 130r / min. When the temperature reaches 45℃, add 3kg XT 100 type methyl methacrylate-butadiene-styrene terpolymer, maintain the temperature at 45℃-52℃, stir for 0.5h, then pour 91kg MF-3285 type trifunctional alicyclic epoxy resin into the reactor, continue stirring for 1.0h, cool to room temperature, and the obtained light yellow viscous liquid is Agent B of the high permeability sand consolidating agent.
[0030] Example 2 The performance index test of the sand consolidation agent sample is as follows Table 2
[0031] Table 2
[0032] project index Cemented core compressive strength (60℃, 48h, MPa) 6.4 High temperature cemented core compressive strength (300℃, 48h, MPa) 5.8 Permeability retention rate (60℃, 24h, %) 81 <![CDATA[Core permeability after cementation (60 °C, 24 h, 10 -3 μm 2 )]]> 457 <![CDATA[Core permeability after high-temperature cementation (300 °C, 24 h, 10 -3 μm 2 )]]> 549
[0033] Embodiment three:
[0034] The sand consolidating agent is divided into A and B. A and B are independent of each other during production but are used in combination. A comprises the following components: 68 kg N,N',N"-trimethyldiethylenetriamine, 20 kg deionized water, 5 kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine, 7 kg N,N,N',N'-tetramethyl-1,3-butanediamine, and the total of the above components is 100 kg; B comprises the following components: 7 kg triethylene glycol monobutyl ether, 4kg of XT 100 type methyl methacrylate-butadiene-styrene terpolymer, 89kg of MF-3285 type trifunctional alicyclic epoxy resin, and the total weight of the above components is 100kg.
[0035] Obtained as follows:
[0036] Weigh the raw materials according to the ratio, pour 68kg N,N',N"-trimethyldiethylenetriamine into the reactor, start stirring at a speed of 80r / min, keep the temperature at 25℃-35℃, add 20kg deionized water and then 5kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine into the reactor, stir for 0.5h, then add 7kg N,N,N',N'-tetramethyl-1,3-butanediamine, continue stirring for 1.0h, and the light yellow micro-colloidal liquid obtained is the A agent of the high permeability sand consolidating agent;
[0037] Weigh the raw materials according to the ratio, add 7kg of triethylene glycol monobutyl ether into the reactor, start heating, and start stirring at a speed of 130r / min. When the temperature reaches 45℃, add 4kg XT 100 type methyl methacrylate-butadiene-styrene terpolymer, maintain the temperature at 45℃-52℃, stir for 0.5h, then pour 89kg MF-3285 type trifunctional alicyclic epoxy resin into the reactor, continue stirring for 1.0h, cool to room temperature, and the obtained light yellow viscous liquid is Agent B of the high permeability sand consolidating agent.
[0038] Example 3 The performance index test of the sand consolidation agent sample is as follows Table 3
[0039] Table 3
[0040] project index Cemented core compressive strength (60℃, 48h, MPa) 6.2 High temperature cemented core compressive strength (300℃, 48h, MPa) 5.8 Permeability retention rate (60℃, 24h, %) 84 <![CDATA[Core permeability after cementation (60 °C, 24 h, 10 -3 μm 2 )]]> 466 <![CDATA[Core permeability after high-temperature cementation (300 °C, 24 h, 10 -3 μm 2 )]]> 573
[0041] It can be seen from the test results of the samples in Examples 1, 2 and 3 that within a certain range, when the addition amount of EHSB-40 erucic acid amide propyl hydroxysulfobetaine and N,N,N',N'-tetramethyl-1,3-butanediamine increases, the core permeability and permeability retention rate will increase accordingly, while the compressive strength will decrease.
[0042] Embodiment 4:
[0043] The sand-fixing agent is divided into A and B. A and B are independent of each other in production but are used in combination. A comprises the following components: 68 kg of diethylenetriamine, 20 kg of deionized water, 5 kg of EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine, 7 kg of N,N,N',N'-tetramethyl-1,3-butanediamine, and the total of the above components is 100 kg; B comprises the following components: 7 kg of triethylene glycol monobutyl ether, 4kg of XT 100 type methyl methacrylate-butadiene-styrene terpolymer, 89kg of MF-3285 type trifunctional alicyclic epoxy resin, and the total weight of the above components is 100kg.
[0044] Obtained as follows:
[0045] Weigh the raw materials according to the ratio, pour 68kg of diethylenetriamine into the reactor, and start stirring at a speed of 80r / min, keep the temperature at 25℃-35℃, add 20kg of deionized water and then 5kg of EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine into the reactor, stir for 0.5h, then add 7kg of N,N,N',N'-tetramethyl-1,3-butanediamine, continue stirring for 1.0h, and the light yellow micro-colloidal liquid obtained is the A agent of the sand consolidating agent;
[0046] Weigh the raw materials according to the ratio, add 7kg of triethylene glycol monobutyl ether into the reactor, start heating, and start stirring at a speed of 130r / min. When the temperature reaches 45℃, add 4kg XT 100 type methyl methacrylate-butadiene-styrene terpolymer, maintain the temperature at 45℃-52℃, stir for 0.5h, then pour 89kg MF-3285 type trifunctional alicyclic epoxy resin into the reactor, continue stirring for 1.0h, cool to room temperature, and the obtained light yellow viscous liquid is Agent B of the sand consolidating agent.
[0047] Example 4 The performance index test of the sand consolidation agent sample is as follows Table 4
[0048] Table 4
[0049] project index Cemented core compressive strength (60℃, 48h, MPa) 6.5 High temperature cemented core compressive strength (300℃, 48h, MPa) 5.9 Permeability retention rate (60℃, 24h, %) 66 <![CDATA[Core permeability after cementation (60°C, 24 h, 10 -3 μm 2 )]]> 345 <![CDATA[Core permeability after high-temperature cementation (300 °C, 24 h, 10 -3 μm 2 )]]> 407
[0050] Compared with Example 3, the sand consolidating agent prepared in Example 4 replaces the raw material of the curing main agent in Agent A from N,N',N"-trimethyldiethylenetriamine with the commonly used curing agent raw material diethylenetriamine. The test results show that using diethylenetriamine as the curing main agent of the present application can slightly improve the compressive strength of the core, but will greatly reduce the permeability and permeability retention rate of the core. This may be because the steric hindrance of diethylenetriamine is small, and the curing reaction intensity with MF-3285 trifunctional alicyclic epoxy resin is higher, which hinders the pore-increasing effect of the pore-increasing agent from the source.
[0051] Embodiment five:
[0052] The sand consolidating agent is divided into A and B. A and B are independent of each other in production but are used in combination. A comprises the following components: 70 kg N,N',N"-trimethyldiethylenetriamine, 24 kg deionized water, 6 kg N,N,N',N'-tetramethyl-1,3-butanediamine, and the total of the above components is 100 kg; B comprises the following components: 6 kg triethylene glycol monobutyl ether, 3kg of XT 100 type methyl methacrylate-butadiene-styrene terpolymer, 91kg of MF-3285 type trifunctional alicyclic epoxy resin, and the total weight of the above components is 100kg.
[0053] Obtained as follows:
[0054] Weigh the raw materials according to the ratio, pour 70kg N,N',N"-trimethyldiethylenetriamine into the reactor, and start stirring at a speed of 80r / min, keep the temperature at 25℃-35℃, add 24kg deionized water into the reactor, stir it into a light yellow uniform liquid, then add 6kg N,N,N',N'-tetramethyl-1,3-butanediamine, continue stirring for 0.5h, and the light yellow transparent liquid obtained is Agent A of the sand consolidating agent;
[0055] Weigh the raw materials according to the ratio, add 6kg of triethylene glycol monobutyl ether into the reactor, start heating, and start stirring at a speed of 130r / min. When the temperature reaches 45℃, add 3kg XT 100 type methyl methacrylate-butadiene-styrene terpolymer, maintain the temperature at 45℃-52℃, stir for 0.5h, then pour 91kg MF-3285 type trifunctional alicyclic epoxy resin into the reactor, continue stirring for 1.0h, cool to room temperature, and the obtained light yellow viscous liquid is Agent B of the sand consolidating agent.
[0056] Example 5 The performance index test of the sand consolidation agent sample is as follows Table 5
[0057] Table 5
[0058] project index Cemented core compressive strength (60℃, 48h, MPa) 6.2 High temperature cemented core compressive strength (300℃, 48h, MPa) 5.8 Permeability retention rate (60℃, 24h, %) 70 <![CDATA[Core permeability after cementation (60 °C, 24 h, 10 -3 μm 2 )]]> 382 <![CDATA[Core permeability after high-temperature cementation (300 °C, 24 h, 10 -3 μm 2 )]]> 459
[0059] Compared with Example 2, the sand consolidating agent prepared in Example 5 replaces the raw material EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine, which is the main pore-increasing agent in Agent A, with deionized water. The test results show that if EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine is not added in this application, the obtained core permeability and permeability retention rate will be significantly reduced.
[0060] Embodiment six:
[0061] The sand consolidating agent is divided into A and B. A and B are independent of each other in production but used in combination. A comprises the following components: 68 kg N,N',N"-trimethyldiethylenetriamine, 20 kg triethylene glycol monobutyl ether, 5 kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine, 7 kg N,N,N',N'-tetramethyl-1,3-butanediamine, and the total of the above components is 100 kg; B comprises the following components: 7 kg triethylene glycol monobutyl ether, 4kg of XT 100 type methyl methacrylate-butadiene-styrene terpolymer, 89kg of MF-3285 type trifunctional alicyclic epoxy resin, and the total weight of the above components is 100kg.
[0062] Obtained as follows:
[0063] Weigh the raw materials according to the ratio, pour 68kg N,N',N"-trimethyldiethylenetriamine into the reactor, start stirring at a speed of 80r / min, keep the temperature at 25℃-35℃, add 20kg triethylene glycol monobutyl ether and then 5kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine into the reactor, stir for 0.5h, then add 7kg N,N,N',N'-tetramethyl-1,3-butanediamine, continue stirring for 0.5h, and the light yellow transparent liquid obtained is Agent A of the sand consolidating agent;
[0064] Weigh the raw materials according to the ratio, add 7kg of triethylene glycol monobutyl ether into the reactor, start heating, and start stirring at a speed of 130r / min. When the temperature reaches 45℃, add 4kg XT 100 type methyl methacrylate-butadiene-styrene terpolymer, maintain the temperature at 45℃-52℃, stir for 0.5h, then pour 89kg MF-3285 type trifunctional alicyclic epoxy resin into the reactor, continue stirring for 1.0h, cool to room temperature, and the obtained light yellow viscous liquid is Agent B of the sand consolidating agent.
[0065] Example 6 The performance index test of the sand consolidation agent sample is as follows Table 6
[0066] Table 6
[0067] project index Cemented core compressive strength (60℃, 48h, MPa) 6.4 High temperature cemented core compressive strength (300℃, 48h, MPa) 5.9 Permeability retention rate (60℃, 24h, %) 72 <![CDATA[Core permeability after cementation (60 °C, 24 h, 10 -3 μm 2 )]]> 395 <![CDATA[Core permeability after high-temperature cementation (300 °C, 24 h, 10 -3 μm 2 )]]> 478
[0068] Compared with Example 3, the sand consolidating agent prepared in Example 6 replaces the deionized water in Agent A with triethylene glycol monobutyl ether. The test results show that the core permeability and permeability retention rate also decreased significantly. Based on the test results of the sample in Example 5, we speculate that the pore-increasing effect of EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine in this sand consolidating agent is closely related to its micellization effect in an aqueous system.
[0069] Embodiment seven:
[0070] The sand consolidating agent is divided into A and B. A and B are independent of each other during production but are used in combination. A comprises the following components: 76 kg N,N',N"-trimethyldiethylenetriamine, 20 kg deionized water, 4 kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine, and the total of the above components is 100 kg; B comprises the following components: 6 kg triethylene glycol monobutyl ether, 3kg of XT 100 type methyl methacrylate-butadiene-styrene terpolymer, 91kg of MF-3285 type trifunctional alicyclic epoxy resin, and the total weight of the above components is 100kg.
[0071] Obtained as follows:
[0072] Weigh the raw materials according to the ratio, pour 76kg N,N',N"-trimethyldiethylenetriamine into the reactor, start stirring at a speed of 80r / min, keep the temperature at 25℃-35℃, add 20kg deionized water and then 4kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine into the reactor, stir for 1.0h, and the light yellow micro-colloidal liquid obtained is the A agent of the sand consolidating agent;
[0073] Weigh the raw materials according to the ratio, add 6kg of triethylene glycol monobutyl ether into the reactor, start heating, and start stirring at a speed of 130r / min. When the temperature reaches 45℃, add 3kg XT 100 type methyl methacrylate-butadiene-styrene terpolymer, maintain the temperature at 45℃-52℃, stir for 0.5h, then pour 91kg MF-3285 type trifunctional alicyclic epoxy resin into the reactor, continue stirring for 1.0h, cool to room temperature, and the obtained light yellow viscous liquid is Agent B of the sand consolidating agent.
[0074] Example 7 The performance index test of the sand consolidation agent sample is as follows Table 7
[0075] Table 7
[0076] project index Cemented core compressive strength (60℃, 48h, MPa) 6.4 High temperature cemented core compressive strength (300℃, 48h, MPa) 5.9 Permeability retention rate (60℃, 24h, %) 75 <![CDATA[Core permeability after cementation (60 °C, 24 h, 10 -3 μm 2 )]]> 427 <![CDATA[Core permeability after high-temperature cementation (300 °C, 24 h, 10 -3 μm 2 )]]> 495
[0077] Compared with Example 2, the sand consolidating agent prepared in Example 7 replaces the raw material of N,N,N',N'-tetramethyl-1,3-butanediamine in Agent A with an equal amount of N,N',N"-trimethyldiethylenetriamine. As a result, the core permeability and permeability retention rate decreased. This shows that adding an appropriate amount of N,N,N',N'-tetramethyl-1,3-butanediamine in this application can help EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine to play a better pore-increasing role. This may be because N,N,N',N'-tetramethyl-1,3-butanediamine has a good steric hindrance effect, which can reduce the spatial density of the resin curing reaction to a certain extent.
[0078] Embodiment eight:
[0079] The sand consolidating agent is divided into A and B. A and B are independent of each other during production but are used in combination. A comprises the following components: 68 kg of N,N',N"-trimethyldiethylenetriamine, 20 kg of deionized water, 5 kg of EHSB-40 erucic acid amide propyl hydroxysulfobetaine, 7 kg of N,N,N',N'-tetramethyl-1,3-butanediamine, and the total weight of the above components is 100 kg; B comprises the following components: 11 kg of triethylene glycol monobutyl ether, 89 kg of MF-3285 trifunctional alicyclic epoxy resin, and the total weight of the above components is 100 kg.
[0080] Obtained as follows:
[0081] Weigh the raw materials according to the ratio, pour 68kg N,N',N"-trimethyldiethylenetriamine into the reactor, start stirring at a speed of 80r / min, keep the temperature at 25℃-35℃, add 20kg deionized water and then 5kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine into the reactor, stir for 0.5h, then add 7kg N,N,N',N'-tetramethyl-1,3-butanediamine, continue stirring for 1.0h, and the light yellow micro-colloidal liquid obtained is the A agent of the sand consolidating agent;
[0082] Weigh the raw materials according to the ratio, add 11kg of triethylene glycol monobutyl ether into the reactor, start heating, and start stirring at a speed of 130r / min. When the temperature reaches 45°C, pour in 89kg of MF-3285 trifunctional alicyclic epoxy resin, maintain the temperature at 45°C-52°C, stir for 0.5h, and cool to room temperature. The resulting light yellow viscous liquid is Agent B of the sand consolidating agent.
[0083] Example 8 The performance index test of the sand consolidation agent sample is as follows Table 8
[0084] Table 8
[0085] project index Cemented core compressive strength (60℃, 48h, MPa) 5.5 High temperature cemented core compressive strength (300℃, 48h, MPa) 4.3 Permeability retention rate (60℃, 24h, %) 83 <![CDATA[Core permeability after cementation (60 °C, 24 h, 10 -3 μm 2 )]]> 457 <![CDATA[Core permeability after high-temperature cementation (300 °C, 24 h, 10 -3 μm 2 )]]> 562
[0086] Compared with Example 3, the sand consolidating agent prepared in Example 8 has XT 100 methyl methacrylate-butadiene-styrene terpolymer was replaced with triethylene glycol monobutyl ether. The test results showed that when this application was not added The compressive strength of the cemented cores with XT 100 methyl methacrylate-butadiene-styrene terpolymer decreased, which may be related to The toughening effect of XT 100 methyl methacrylate-butadiene-styrene terpolymer is related.
[0087] Embodiment nine:
[0088] The sand consolidating agent is divided into A and B. A and B are independent of each other during production but are used in combination. A comprises the following components: 68 kg N,N',N"-trimethyldiethylenetriamine, 20 kg deionized water, 5 kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine, 7 kg N,N,N',N'-tetramethyl-1,3-butanediamine, and the total of the above components is 100 kg; B comprises the following components: 7 kg triethylene glycol monobutyl ether, 4kg of XT 100 type methyl methacrylate-butadiene-styrene terpolymer, 89kg of E-51 type epoxy resin, and the total weight of the above components is 100kg.
[0089] Obtained as follows:
[0090] Weigh the raw materials according to the ratio, pour 68kg N,N',N"-trimethyldiethylenetriamine into the reactor, start stirring at a speed of 80r / min, keep the temperature at 25℃-35℃, add 20kg deionized water and then 5kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine into the reactor, stir for 0.5h, then add 7kg N,N,N',N'-tetramethyl-1,3-butanediamine, continue stirring for 1.0h, and the light yellow micro-colloidal liquid obtained is the A agent of the sand consolidating agent;
[0091] Weigh the raw materials according to the ratio, add 7kg of triethylene glycol monobutyl ether into the reactor, start heating, and start stirring at a speed of 130r / min. When the temperature reaches 45℃, add 4kg XT 100 type methyl methacrylate-butadiene-styrene terpolymer, maintain the temperature at 45℃-52℃, stir for 0.5h, then pour 89kg of E-51 type epoxy resin into the reactor, continue stirring for 1.0h, cool to room temperature, and the obtained light yellow viscous liquid is Agent B of the sand consolidating agent.
[0092] Example 9 The performance index test of the sand consolidation agent sample is as follows Table 9
[0093] Table 9
[0094] project index Cemented core compressive strength (60℃, 48h, MPa) 5.0 High temperature cemented core compressive strength (300℃, 48h, MPa) 2.9 Permeability retention rate (60℃, 24h, %) 89 <![CDATA[Core permeability after cementation (60 °C, 24 h, 10 -3 μm 2 )]]> 489 <![CDATA[Core permeability after high-temperature cementation (300 °C, 24 h, 10 -3 μm 2 )]]> 611
[0095] Compared with Example 3, the sand consolidating agent prepared in Example 9 replaces the MF-3285 trifunctional alicyclic epoxy resin in Agent B with the E-51 epoxy resin commonly used in sand consolidating agents. The results show that the compressive strength of the obtained cemented core decreases significantly, especially under high temperature conditions, the decrease is too large to basically meet the use requirements. This may be because the curing reaction activity of E-51 epoxy resin is not as good as that of MF-3285 trifunctional alicyclic epoxy resin, and the curing reaction strength with N,N',N"-trimethyldiethylenetriamine with some steric hindrance is not high enough. The decrease in bonding strength brings about a slight increase in the permeability of the cemented core, which can also prove from the side that the sand consolidating agent A of the present application does have a good effect in maintaining permeability.
[0096] Embodiment ten:
[0097] The sand consolidating agent is divided into A and B. A and B are independent of each other during production but are used in combination. A comprises the following components: 75 kg of N,N,N',N'-tetramethyl-1,3-butanediamine, 20 kg of deionized water, 5 kg of EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine, and the total of the above components is 100 kg; B comprises the following components: 7 kg of triethylene glycol monobutyl ether, 4kg of XT 100 type methyl methacrylate-butadiene-styrene terpolymer, 89kg of MF-3285 type trifunctional alicyclic epoxy resin, and the total weight of the above components is 100kg.
[0098] Obtained as follows:
[0099] Weigh the raw materials according to the ratio, pour 75kg N,N,N',N'-tetramethyl-1,3-butanediamine into the reactor, start stirring at a speed of 80r / min, keep the temperature at 25℃-35℃, add 20kg deionized water and then 5kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine into the reactor, stir for 1.0h, and the light yellow micro-colloidal liquid obtained is the A agent of the sand consolidating agent;
[0100] Weigh the raw materials according to the ratio, add 7kg of triethylene glycol monobutyl ether into the reactor, start heating, and start stirring at a speed of 130r / min. When the temperature reaches 45℃, add 4kg XT 100 type methyl methacrylate-butadiene-styrene terpolymer, maintain the temperature at 45℃-52℃, stir for 0.5h, then pour 89kg MF-3285 type trifunctional alicyclic epoxy resin into the reactor, continue stirring for 1.0h, cool to room temperature, and the obtained light yellow viscous liquid is Agent B of the sand consolidating agent.
[0101] Example 10 The performance index test of the sand consolidation agent sample is as follows Table 10
[0102] project index Cemented core compressive strength (60℃, 48h, MPa) 3.2 High temperature cemented core compressive strength (300℃, 48h, MPa) 1.1
[0103] Compared with Example 3, the sand consolidating agent prepared in Example 10 replaces the raw material of N,N',N"-trimethyldiethylenetriamine of the main curing agent in Agent A with N,N,N',N'-tetramethyl-1,3-butanediamine, that is, Example 10 uses N,N,N',N'-tetramethyl-1,3-butanediamine as the main curing agent and does not contain N,N',N"-trimethyldiethylenetriamine. However, after testing the compressive strength of the obtained cemented core, it was found that the result was not ideal and could not meet the use requirements, so the permeability related indicators were not tested again. It is speculated that the reason may be that the two amine groups in N,N,N',N'-tetramethyl-1,3-butanediamine are tertiary amines, and the steric hindrance is too large, which affects the activity of the curing reaction, resulting in poor bonding strength of the cemented core.
[0104] Embodiment eleven:
[0105] The sand consolidating agent is divided into A and B. A and B are independent of each other during production but are used in combination. A comprises the following components: 68 kg N,N',N"-trimethyldiethylenetriamine, 20 kg deionized water, 5 kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine, 7 kg N,N,N',N'-tetramethyl-1,3-butanediamine, and the total of the above components is 100 kg; B comprises the following components: 7 kg triethylene glycol monobutyl ether, 4kg of XT 100 type methyl methacrylate-butadiene-styrene terpolymer, 89kg of cyclohexane-1,2-dicarboxylic acid diglycidyl ester, and the total weight of the above components is 100kg.
[0106] Obtained as follows:
[0107] Weigh the raw materials according to the ratio, pour 68kg N,N',N"-trimethyldiethylenetriamine into the reactor, start stirring at a speed of 80r / min, keep the temperature at 25℃-35℃, add 20kg deionized water and then 5kg EHSB-40 erucic acid amide propyl hydroxysulfonyl betaine into the reactor, stir for 0.5h, then add 7kg N,N,N',N'-tetramethyl-1,3-butanediamine, continue stirring for 1.0h, and the light yellow micro-colloidal liquid obtained is the A agent of the sand consolidating agent;
[0108] Weigh the raw materials according to the ratio, add 7kg of triethylene glycol monobutyl ether into the reactor, start heating, and start stirring at a speed of 130r / min. When the temperature reaches 45℃, add 4kg XT 100 type methyl methacrylate-butadiene-styrene terpolymer, maintain the temperature at 45℃-52℃, stir for 0.5h, then pour 89kg of cyclohexane-1,2-dicarboxylic acid diglycidyl ester into the reactor, continue stirring for 1.0h, cool to room temperature, and the obtained light yellow viscous liquid is Agent B of the sand consolidating agent.
[0109] Example 11 The performance index test of the sand consolidation agent sample is as follows Table 11
[0110] project index Cemented core compressive strength (60℃, 48h, MPa) 4.0 High temperature cemented core compressive strength (300℃, 48h, MPa) 2.7 Permeability retention rate (60℃, 24h, %) 90 <![CDATA[Core permeability after cementation (60 °C, 24 h, 10 -3 μm 2 )]]> 502 <![CDATA[Core permeability after high-temperature cementation (300 °C, 24 h, 10 -3 μm 2 )]]> 637
[0111] Compared with Example 3, the sand consolidating agent prepared in Example 11 replaces the MF-3285 trifunctional alicyclic epoxy resin in Agent B with cyclohexane-1,2-dicarboxylic acid diglycidyl ester, which has a similar structure. The results show that the compressive strength of the obtained cemented core is still much worse, but the permeability performance index is better. It is speculated that the reason may be that cyclohexane-1,2-dicarboxylic acid diglycidyl ester has one less ethylene oxide at the end connected to cyclohexane compared to MF-3285 trifunctional alicyclic epoxy resin, resulting in the strength of its curing and cross-linking reaction with N,N',N"-trimethyldiethylenetriamine with some steric hindrance being significantly inferior to that of MF-3285 trifunctional alicyclic epoxy resin.
[0112] The above description of the embodiments is to facilitate the understanding and use of the present invention by those of ordinary skill in the art. It is obvious that those familiar with the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments. Improvements and modifications made by those skilled in the art based on the principles of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention. The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high permeability sand consolidating agent, characterized in that: The sand consolidating agent comprises an agent A and an agent B, wherein the agent A comprises the following components: N,N',N"-trimethyldiethylenetriamine, deionized water, amidopropylhydroxysulfonyl betaine viscoelastic surfactant and N,N,N',N'-tetramethyl-1,3-butanediamine; and the agent B comprises the following components: triethylene glycol monobutyl ether, methyl methacrylate-butadiene-styrene terpolymer and MF-3285 trifunctional alicyclic epoxy resin.
2. A high permeability sand consolidating agent, characterized in that: The sand consolidating agent comprises an agent A and an agent B. By weight percentage, the agent A comprises the following components: 67%-70% of N,N',N"-trimethyldiethylenetriamine, 19%-21% of deionized water, 4%-5% of amidopropylhydroxysulfonyl betaine viscoelastic surfactant, 6%-8% of N,N,N',N'-tetramethyl-1,3-butanediamine, and the total of the above components is 100%; the agent B comprises the following components: 6%-10% of triethylene glycol monobutyl ether, 3%-4% of methyl methacrylate-butadiene-styrene terpolymer, and 86%-91% of MF-3285 trifunctional alicyclic epoxy resin, and the total of the above components is 100%.
3. The high permeability sand consolidating agent according to claim 2, characterized in that: The amidopropyl hydroxysulfonyl betaine viscoelastic surfactant is selected from erucic acid amidopropyl hydroxysulfonyl betaine.
4. The high permeability sand consolidating agent according to claim 3, characterized in that: The concentration of the erucamidopropyl hydroxysulfobetaine is 40%.
5. The high permeability sand consolidating agent according to claim 4, characterized in that: The mass ratio of agent A to agent B in the sand consolidating agent is 1.00:(1.06-1.33).
6. The method for preparing the high permeability sand consolidating agent according to any one of claims 2 to 5, characterized in that: The steps include: Production process of agent A: weigh the raw materials according to the ratio, pour N,N',N"-trimethyldiethylenetriamine into the reactor, and start stirring at a speed of 60r-100r / min, keep the temperature at 15℃-40℃, add deionized water and amidopropyl hydroxysulfonyl betaine viscoelastic surfactant to the reactor, stir for 0.5-1.0h, then add N,N,N',N'-tetramethyl-1,3-butanediamine, continue stirring for 0.5-1.0h, and the light yellow micro-colloidal liquid obtained is agent A of high permeability sand consolidating agent; Production process of Agent B: Weigh the raw materials according to the ratio, add triethylene glycol monobutyl ether into the reactor, start heating, and start stirring at a speed of 90r-130r / min. When the temperature reaches 45°C, add methyl methacrylate-butadiene-styrene terpolymer, maintain the temperature at 45°C-52°C, stir for 0.5-1.0h, then pour MF-3285 trifunctional alicyclic epoxy resin into the reactor, continue stirring for 0.5-1.0h, cool to room temperature, and the resulting light yellow viscous liquid is Agent B of the high permeability sand consolidating agent.
7. Use of the high-permeability sand-fixing agent according to any one of claims 1 to 5 or the high-permeability sand-fixing agent prepared by the method according to claim 6 in oil well sand control.
8. The use according to claim 7, characterized in that: The method comprises the following steps: mixing agent A and agent B of a sand consolidating agent in a mass ratio of 1.00:(1.06-1.33).
Citation Information
Patent Citations
Modified resin sand consolidation agent as well as preparation method and application thereof
CN103013485A
Active oil-washing sand consolidating agent and preparation method and application thereof
CN106590562A
Sand consolidation agent for oil field and preparation method of sand consolidation agent
CN112877048A
Low-temperature sand consolidation working fluid system as well as preparation method and application thereof
CN117004379A
consolidation of sands
FR1436172A